Biologically inspired cognitive architectures (BICA) for young scientists : proceedings of the First International Early Research Career Enhancement School on BICA and Cybersecurity (FIERCES 2017) /: proceedings of the First International Early Research Career Enhancement School on BICA and Cybersecurity (FIERCES 2017). ([2018]) - Unknown
No abstract available